2021
DOI: 10.1097/qai.0000000000002570
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Related Medical Mistrust, Health Impacts, and Potential Vaccine Hesitancy Among Black Americans Living With HIV

Abstract: Background: Medical mistrust, a result of systemic racism, is prevalent among Black Americans and may play a role in COVID-19 inequities. In a convenience sample of HIV-positive Black Americans, we examined associations of COVID-19-related medical mistrust with COVID-19 vaccine and COVID-19 treatment hesitancy and negative impacts of COVID-19 on antiretroviral therapy (ART) adherence. Methods: Participants were 101 HIV-positive Black Americans (age: M = 50.3 years; SD = 11.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
436
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 414 publications
(462 citation statements)
references
References 49 publications
23
436
1
2
Order By: Relevance
“…The same survey also found that over half (52%) of the survey respondents believed that the U.S. healthcare system "always/often" treats people unfairly based on their race or ethnic background. A recent study by Bogart et al (2021) [125] also found substantial issues of mistrust surrounding COVID-19 vaccines and treatment among HIV-positive Blacks. Their study findings combined with experience and expertise regarding issues of medical mistrust by U.S.…”
Section: Discussionmentioning
confidence: 98%
“…The same survey also found that over half (52%) of the survey respondents believed that the U.S. healthcare system "always/often" treats people unfairly based on their race or ethnic background. A recent study by Bogart et al (2021) [125] also found substantial issues of mistrust surrounding COVID-19 vaccines and treatment among HIV-positive Blacks. Their study findings combined with experience and expertise regarding issues of medical mistrust by U.S.…”
Section: Discussionmentioning
confidence: 98%
“…Due to historical and current interpersonal and systemic racism in the U.S., much of which is propagated at a government and policy level, racial differences in vaccine trust and lower levels of trust among African Americans may also be observed ( Quinn et al, 2016 ; Solomon and Castro, 2019 ; Feagin, 2014; Bogart et al, 2020 ; Ferdinand and Reddy, 2020). For example, an online survey on COVID-19 vaccine attitudes among U.S. adults from Marks, 2020 found that vaccine acceptability differed significantly by sociodemographic characteristics such as race ( Reiter et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…While there is considerable enthusiasm and anticipation for the COVID-19 vaccine, little is known about vaccine hesitancy, especially for COVID-19, in vulnerable French populations. A vulnerable population, as people living with HIV, presents poorer COVID-related outcomes compared to those without HIV [ 28 , 29 , 30 ]. Currently, little evidence exists on how HIV infection affects the risk of poor outcomes from COVID-19 [ 31 ].…”
Section: Introductionmentioning
confidence: 99%